IMMU-52. EFFECTS OF IMMUNE CHECKPOINT BLOCKADE ON ANTIGEN-SPECIFIC CD8+ T CELLS FOR USE IN ADOPTIVE CELLULAR THERAPY. (12th November 2021) - Ogando-Rivas, Elizabeth; Castillo, Paul; Jones, Noah; Trivedi, Vrunda; Drake, Jeffrey; Dechkovskaia, Anjelika; Candelario, Kate; Yang, Changlin; Mitchell, Duane
Abstract: BACKGROUND: Adoptive T-cell therapies have been successfully used as treatment for patients diagnosed with advanced cancers. Unfortunately, for some refractory cancers, they have failed. To overcome this, checkpoint inhibitors have shown to rescue immune anti-tumor responses. We hypothesized that in-vitro checkpoint blockade during T-cell stimulation and expansion with RNA-pulsed dendritic cells may enhance the activity of antigen-specific T-cells and improve the efficacy of ACT platforms. METHODS: Human PBMCs were isolated from CMV seropositive donors to generate DCs and pulsed them with CMVpp65-mRNA to educate T-cells in co-culture for 15-days. We targeted pp65 antigen which is ubiquitously expressed by glioblastoma cells. Three checkpoint blockade conditions were evaluated (anti-PD1, anti-Tim3 and anti-PD1+Tim3). IL2 was added every 3 days as well as the blockade antibodies. Immunephenotyping was performed on Day-0 and Day-15. Polyfunctional antigen specific responses were evaluated upon rechallenge with CMVpp65 peptides. RESULTS: CMVpp65 activated CD8 + T-cells upregulate Lag3 and Tim3 (p= < 0.0001). Tim3 blockade alone or in combination led to a significant upregulation of Lag3 expression on CD8 + pp65Tetramer + central memory, effector memory, and TEMRA T-cells. This latter T-cell subset uniquely maintain double-positive Tim3/Lag3 expression after blockade. In contrast, PD-1 blockade had minimal effects on Tim3 or Lag3 expression. In addition, IFN-g secretion was reduced in T-cells treated with Tim3 blockade in a dose-dependent manner (p= 0.004). CONCLUSION: In this study, we have identified a potential activating component of Tim3 and linkage between Tim3 and Lag3 signaling upon blocking Tim3 axis during T-cell antigen presenting cell interactions that should be considered when targeting immune checkpoints for clinical use.